PENGEMBANGAN MODEL PEMBELAJARAN TEKNIK DASAR DRIBBLE BOLA BASKET UNTUK SISWA SEKOLAH MENENGAH ATAS - Indhi Ilham Farias; Dian Estu Prasetyo; Alchonity Harika Fitri (Dharmas Journal of Sport, 2022)
The problem of this research is the low dribbling ability of students in basketball games. The low dribbling ability of students in playing basketball can be seen in every dribbling opportunity, many students fail. The failure of students to dribble the ball in a basketball game is caused by the player not being able to dribble the ball well. The ball tends to escape from student control. Students cannot dribble while running agilely. The lack of a dribble learning model for students will have an impact on student success during lessons about basketball. This study aims to develop a basic basketball dribble technique learning model with valid, practical, and effective criteria. This study uses the Research and Development (R&D) method used to produce the product, this study uses the development method and the ADDIE model procedure, namely the analysis, design, development, implementation, and evaluation stages. In this study the development of data collection instruments in the form of Validation, Practicality and Effectiveness sheets. The results of this study are seen from the practical results obtained from the homeroom teacher and 20 students, that from the basic technique learning model of Basketball Dribble that the researchers made has gained practicality. And judging from the results of the practice test that was completed using the basic technique learning model of Basketball Dribble, it obtained 80% completeness in the very effective category.